Pengaruh Ekuitas Merek terhadap Loyalitas Merek yang dimediasi oleh Kepuasan Pelanggan Pada Produk Perawatan Wajah Somethinc di Kota Payakumbuh - hafsah, siti; jauharry, jauharry (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of consumer dimension brand equity on brand loyalty mediated by customer satisfaction in Somethinc facial care products in Payakumbuh City. The sampling technique is non-probability sampling with purposive sampling method. The number of samples in this study were 150 respondents. The research uses a quantitative approach then the data is analyzed using the PLS-SEM method with the help of SmartPLS version 3 software. The results show that perceived quality, brand trust, and lifestyle suitability have a significant effect on customer satisfaction, perceived value and brand identification have no significant effect on customer satisfaction, customer satisfaction has a significant effect on brand loyalty. Customer satisfaction has a significant effect as a mediation between perceived quality, brand trust, and lifestyle suitability on brand loyalty but has no significant effect between perceived value and brand identification on brand loyalty. The implication of this research is that companies can pay attention to the ingredients of Something's products that are guaranteed quality and know the lifestyle of customers in caring for their faces so that customers will always use Somethinc's products because they meet their expectations and desires.